2023
DOI: 10.3389/fnagi.2023.1084136
|View full text |Cite
|
Sign up to set email alerts
|

Associations between trajectories of cardiovascular risk factor change and cognitive impairment in Chinese elderly: A nationwide cohort study

Abstract: ObjectivesThis study aimed to investigate the relationship between long-term trajectories of changes in cardiovascular risk factors (CVRFs) and the risk of cognitive impairment among Chinese adults over 60 years old.MethodsData were obtained from the Chinese Longitudinal Healthy Longevity Survey 2005–2018. Cognitive function was evaluated longitudinally through the Chinese version of the Mini-Mental State Examination (C-MMSE), and cognitive impairment (C-MMSE ≤23) was used as the main outcome variable. The car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Mostly, the study subjects belonged to the older age group, consistent with current literature which supports that clinical CVD and CI often coexist in the aging populations, and relates with increased risk of CI [30,31]. A community-based study in Taiwan found that healthy, middle-aged, and older adults, with moderate-to-high CVRF burden, were signi cantly linked to dementia and CI (verbal memory and language), indicating a strong relationship between CI and CVD risk burden The number of female subjects with CVD was found to be a bit higher but not signi cant.…”
Section: Discussionsupporting
confidence: 88%
“…Mostly, the study subjects belonged to the older age group, consistent with current literature which supports that clinical CVD and CI often coexist in the aging populations, and relates with increased risk of CI [30,31]. A community-based study in Taiwan found that healthy, middle-aged, and older adults, with moderate-to-high CVRF burden, were signi cantly linked to dementia and CI (verbal memory and language), indicating a strong relationship between CI and CVD risk burden The number of female subjects with CVD was found to be a bit higher but not signi cant.…”
Section: Discussionsupporting
confidence: 88%